A Combined Approach of Simulation and Analytic Hierarchy Process in Assessing Production Facility Layouts - Ramli, Razamin; Cheng, Kok Meng (2013)
One of the important areas of concern in order to obtain a competitive level of productivity in a manufacturing system is the layout design and material transportation system (conveyor system). However, changes in customers’ requirements have triggered the need to design other alternatives of the manufacturing layout for existing production floor. Hence, this paper discusses effective alternatives of the process layout specifically, the conveyor system layout. Subsequently, two alternative designs for the conveyor system were proposed with the aims to increase the production output and minimize space allocation. The first proposed layout design includes the installation of conveyor oven in the particular manufacturing room based on priority, and the second one is the one without the conveyor oven in the layout. Simulation technique was employed to design the new facility layout. Eventually, simulation experiments were conducted to understand the performance of each conveyor layout design based on operational characteristics, which include predicting the output of layouts. Utilizing the Analytic Hierarchy Process (AHP), the newly and improved layout designs were assessed before the final selection was done. As a comparison, the existing conveyor system layout was included in the assessment process. Relevant criteria involved in this layout design problem were identified as (i) usage of space of each design, (ii) operator’s utilization rates, (iii) return of investment (ROI) of the layout, and (iv) output of the layout. In the final stage of AHP analysis, the overall priority of each alternative layout was obtained and thus, a selection for final use by the management was made based on the highest priority value. This efficient planning and designing of facility layout in a particular manufacturing setting is able to minimize material handling cost, minimize overall production time, minimize investment in equipment, and optimize utilization of space